Analisis Beban Kerja Karyawan di Departemen Produksi Menggunakan Metode Full Time Equivalent (FTE) PT. KLM (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to analyze the workload level of employees in the production department of PT. KLM using the Full-Time Equivalent (FTE) method. This method is used to determine the optimal number of workers required to complete a task by considering the total workload and available working time. The results of the analysis show that operators in painting, finishing, sandblasting, PPIC (Production Planning and Inventory Control), and Quality Control are categorized as optimal or have a normal workload. However, welding operators face a shortage of staff, resulting in an underload workload condition, while cutting operators experience an excessive workload with surplus labor. Additionally, the Health, Safety, and Environment (HSE) staff also show an underload workload level
Keywords: Workload analysis, Full-Time Equivalent (FTE), Production department, Overload, Underload